Biomassa e extração de nutrientes por plantas de cobertura - Cavalcante, Valéria S. [UNESP]; Santos, Valdevan R.; Santos Neto, Antônio L. Dos; Santos, Márcio A. L. Dos; Santos, Cícero G. Dos; Costa, Leonardo C. (Departamento de Engenharia Agrícola - UFCG, 2012)
ABSTRACT With the objective of evaluating the biomass production and nutrient removal by plant cover in the Agreste region of Alagoas, an experiment was conducted in the experimental field of the Federal University of Alagoas - Campus Arapiraca. Randomized block design was used, with eight treatments and four replications. The treatments were: Crotalaria juncea, Crotalaria spectabilis, Cajanus cajan (L.) Mill sp., Cajanus cajan, Canavalia ensiformis, Dolichos lablab, Mucuna aterrima and the spontaneous local vegetation (control). The green matter in an area of 1 m2 during the flowering of each species was evaluated, and biomass was then dried in an oven at 65 ºC until constant weight for dry matter, in which the contents of macro and micronutrients were extracted. Leguminous plant showed potential for use as green manure in the Agreste region of Alagoas, with N contents higher than the spontaneous vegetation and not being different from one for the accumulation of P, K, Ca, Mg, S, B, Mn and Zn. The spontaneous vegetation was similar to dry matter of legumes production. Among the treatments Cajanus cajan showed higher dry matter production and N accumulation in the aerial part.

RESUMO Com o objetivo de avaliar a biomassa e a extração de nutrientes por plantas de cobertura no Agreste de Alagoas, implantou-se um experimento no campo experimental da Universidade Federal de Alagoas - Campus Arapiraca. O delineamento experimental adotado foi em blocos casualizados, com oito tratamentos e quatro repetições. Os tratamentos foram: Crotalaria juncea, Crotalaria spectabilis, Cajanus cajan (L.) Millsp., Cajanus cajan, Canavalia ensiforme, Dolichos lablab, Mucuna aterrima e a vegetação espontânea local (testemunha). A matéria verde foi avaliada em uma área de 1 m2 no florescimento de cada espécie sendo, em seguida, a biomassa secada em estufa a 65 ºC até atingir massa constante para obter a matéria seca, em que foram extraídos os teores de macro e micronutrientes. As leguminosas apresentaram potencial para uso como adubo verde na região Agreste de Alagoas, além de teores de N superiores aos da vegetação espontânea não sendo diferentes entre si no acúmulo de P, K, Ca, Mg, S, B, Mn e Zn. A vegetação espontânea foi semelhante às leguminosas na produção de matéria seca. Dentre os tratamentos o Cajanus cajan arbóreo apresentou maior produção de matéria seca e acúmulo de N na parte aérea.
Biomass production and nutrient removal by plant cover
Keywords: green manure; leguminous; macronutrients; micronutrients; adubação verde; leguminosas; macronutrientes; micronutrientes